A critical analysis of purchasing of health services in the Philippines: A case study of PhilHealth - Oscar F. Picazo; Valerie Gilbert T. Ulep; Ida Marie Pantig; Beverly Lorraine Ho (Philippine Institute for Development Studies (PIDS), 2015)
This study is a critical analysis of health services purchasing undertaken by the PhilHealth, which implements the National Health Insurance Program of the Philippines. Purchasing is about how an institution should determine, negotiate for, and obtain health services on behalf of a group of people that has contributed resources, either through taxes, premiums, or point-of-service payments, in exchange for anticipated health services.The study employs a principal/agent framework for analyzing three critical relationships: that between the purchaser and health-care providers, between the purchaser and citizens (or members of Philhealth), and between the purchaser and the government, both as regulator and as funder of services, at the national government and local government levels. The study is an analysis of the key alignments and variances of purchasing practices vis-a-vis the "design" and the theoretical ideal in each of the three relationships. To do this, the study employs an extensive document review as well as key informant interviews of decisionmakers and other stakeholders, including PhilHealth management and staff, the Department of Health, provider representatives, and consumer representatives. It is part of a multicountry analysis of purchasing of health services in selected African and Asian health-financing organizations. It also provides key findings and policy implications.
Keywords: 330; purchasing of health services; Philippines; PhilHealth; strategic purchasing; active purchasing; health care financing